Peranan Pendidik Agama Islam terhadap Peningkatan Kualitas Belajar Peserta Didik di Madrasah Ibtidaiyah Al-Amanah Jeneponto - Rudi Hartono; Al Bazzar (Lembaga Yasin AlSys, 2025)
The strategic role of Islamic Religious Education (PAI) teachers in enhancing the quality of instruction has received considerable attention in various studies; however, comprehensive analyses of their multifaceted roles—as educators, mentors, facilitators, and motivators—within the context of madrasah ibtidaiyah remain limited. This study aims to analyze the role of PAI teachers in improving students’ learning quality at Madrasah Ibtidaiyah Al-Amanah Jeneponto. A descriptive qualitative approach was employed using a case study design. Research informants included the school principal, PAI teachers, and other relevant stakeholders selected through purposive sampling. Data were collected via interviews, observation, and documentation, and analyzed using the Miles and Huberman model, involving data condensation, data display, and conclusion drawing. The findings indicate that PAI teachers fulfill multiple roles: as educators delivering instruction grounded in Islamic values, as mentors shaping students’ character, as facilitators fostering a conducive learning environment, and as motivators enhancing students’ enthusiasm for learning. Supporting factors include the teachers’ relevant academic qualifications and the availability of adequate learning resources. The primary challenge lies in the diverse characteristics of students, necessitating adaptive pedagogical approaches. The study concludes that the holistic role of PAI teachers significantly contributes to the academic and spiritual development of students. The findings underscore the need for educational institutions to strengthen both the pedagogical and religious competencies of PAI teachers to ensure effective, value-oriented learning.